The new system linguistics: toward an ecosystemic linguistics - Strohner, Hans (2019)
A new view of the world is now emerging in the humanities, a view oriented towards the situatedness of human behaviour and which may be conceptualized with the ecosystem metaphor. According to this view, behaviour can be analysed as interaction between organism and environment. From such a general view of behaviour, far-reaching consequences for the modelling of linguistic situatedness and adaptivity are developing. In addition, the ecosystemic orientation of linguistics provides a new methodology for the investigation of linguistic processes as well as new perspectives for the application of linguistics.